ANALISA PENGARUH VISCOSITAS LUMPUR DAN KECEPATAN ALIRAN FLUIDA DENGAN VARIASI SUDUT PIPA ISAP LUMUR TERHADAP KAPASITAS ALIRAN POMPA PENYEDOT LUMPUR - Utomo, Gatut Prijo; Laksana, Ponda (MEKANIKA: Jurnal Teknik Mesin, 2015)
Today we meet in some places of the cities get flood frequently, it is happen due to several things namely the waterways too small that make water flowing exceed from those drainage, waterways clogged cause of pile ofrubbish, as well as waterways become shallow result in mud sedimentation. From the problem mentioned above,then emerge an idea to design simple tools process that is pipeline installation on mud sucker pump.This research aims to analyzes the effect of mud viscosity and fluid current speed in various of mud suck pipe cornertoward capacity of mud sucker pipe the higher of the flow then the higher of current average capacity, then incurrent average speed and the highest current average capacity happen in mud sucker corner 35Â° that is V =2,168 m/s value of Qout = 0.000621 ,m3/s. While the higher of mud viscosity value then lower its current capacity,then otherwise the lower of mud viscosity value then higher its current capacity. In highest average viscosity (ï¨) = 1,3003 N.s/m2, the value of current capacity (Qout) is small happen in mud sucker pipe corner 60Â° = 0,000523 m/s.While smallest viscosity (ï¨) = 1,1225N.s/m2, , the value of current capacity (Q) is big happen in mud sucker pipecorner 35Â° = 0,000621 m3out/s. And the value of current capacity is smaller then output current capacity is bigger,highest mud current capacity (Qin) happen in mud sucker pipe corner 35Â° that is (Qin) = 0,000281 m/s and produceaverage (Qout) as high 0,000621 m3/s.Keywords : Mud sucker pump, mud sucker corner variation